Nyale: Sumba's Typical Polychaeta in Cultural and Science Studies as Authentic Science Learning Materials - Geterudis Kerans; Yayan Sanjaya; Liliasari (Postgraduate, University of Mataram, 2024)
One of Indonesia's local wisdom is Timba Nyale. The Timba Nyale tradition is held every year in March-April, where the people of Sumba flock to the coast while waiting for the appearance of Nyale. This research aims to understand the meaning of Timba Nyale cultural studies and analyze the importance of Science in Nyale to be used as authentic Science learning material. This research was conducted in Buku Bani Village, Ate Dalo Village, Kodi District, Southwest Sumba Regency, East Nusa Tenggara. The method used is a qualitative method using grounded theory. Data collection was done through interviews, observation, documentation, and literature study. The results showed that Nyale has a significant meaning which is a marker for the success or failure of the harvest for the people of Sumba. Nyale in the Sumba tradition also has scientific values, including the importance of preservation and maintaining the conservation of species called Nyale. Analysis of learning outcomes in Animal Anatomy and Physiology courses in one of the private universities in Sumba shows that Nyale can be studied in the practicum of animal anatomy and physiology courses.